PENGEMBANGAN MEDIA BERBASIS RPG MAKER MV UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS VIII SMP - Esra Roida Handayani Marpaung; Glory Indira Diana Purba (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The study employed the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects consisted of 35 Grade VIII students at SMP Negeri 45 Batam. The results indicate that: (1) The average validity scores obtained from material experts (92.86%) and media experts (88.75%) fall within the very valid category. (2) The RPG Maker MV–assisted learning media met the criteria for effectiveness, as evidenced by the classical mastery requirement stipulating that at least 85% of students must achieve a minimum score of 75 based on the KKM standard. In this study, 30 students (85.7%) achieved the minimum required score. (3) Based on teacher and student response questionnaires, the developed media fulfilled the criteria for high practicality, with average percentages of 98.3% and 86.35%, respectively. (4) Students’ mathematical problem-solving abilities showed substantial improvement, with the average score increasing from 32.86 on the pretest to 87.5 on the posttest. An N-Gain value of 0.84 indicates that the improvement lies within the high category.